Jurnal studi ilmu-ilmu al-Qur'an dan Hadis - Universitas Islam Negeri Sunan Kalijaga. Jurusan Tafsir Hadis (Jurusan Tafsir Hadis, Fakultas Ushuluddin, UIN Sunan Kalijaga, 2000)
Study on the interpretation of Koran and Hadith in Indonesia.
Keywords: Qurʼan : Criticism, interpretation, etc : Indonesia : Periodicals; Qurʼan : Study and teaching : Indonesia : Periodicals; Qurʼan; Hadith : Periodicals; Hadith; Education; Indonesia